Şiddetli kaudal regresyon sendromu olan pediatrik bir hastada tek foton emisyonlu bilgisayarlı tomografi/bilgisayarlı tomografi ile hibrid renal kortikal görüntüleme - KESİM, SELİN; TUROĞLU, HALİL TURGUT; ÖZGÜVEN, SALİH; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (My University, 2022)
© 2022 by Turkish Society of Nuclear Medicine Molecular Imaging and Radionuclide Therapy published by Galenos Yayınevi.Caudal regression syndrome (CRS) or sacral agenesis is a rarely seen malformation with a varying degree of structural abnormalities, including multiorgan system dysfunctions, reported with higher incidence among children of mothers with diabetes, as in this case. Spinal anomalies can range from coccyx hemiagenesis to the total absence of lower lumbar vertebrae and sacrum in most severe cases. Herein, we have presented a 9-year-old patient with CRS who had renal failure. Technetium-99m dimercaptosuccinic acid renal scintigraphy revealed bilaterally non-functioning kidneys with no renal cortical uptake. Renal anomalies in CRS with vertebral, anorectal, cardiac, trachea-esophageal, renal, and limb anomalies association include one-sided renal agenesis, multicystic dysplastic kidneys, and ureter duplications.

Kaudal regresyon sendromu (KRS) veya sakral agenezi, çoklu organ sistemlerini etkileyen, yapısal anomaliler ile seyreden ve olgumuzda olduğu gibi diyabetik annelerin çocukları arasında daha yüksek sıklıkta görülen nadir bir malformasyondur. Vertebral anomaliler koksiksin kısmi agenezisinden ağır olgularda sakral ve/veya lomber vertebraların total agenezisine kadar değişebilmektedir. Burada, teknesyum-99m DMSA böbrek sintigrafisinde bilateral kortikal aktivite tutulumu izlenmeyen, non-fonksiyonel böbrekler saptanan KRS tanılı 9 yaşında bir pediatrik vaka sunulmaktadır. Tek taraflı renal agenezi, multisistik displastik böbrekler ve toplayıcı sistem duplikasyonları gibi renal anomaliler KRS ile vertebral, anorektal, kardiyak, trakeoözafagial, renal ve ekstremite anomalileri birlikteliğinde görülebilmektedir.
Hybrid renal cortical imaging with single photon emission computerized tomography/computed tomography in a pediatric patient with severe caudal regression syndrome
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nükleer Tıp; Medicine; Health Sciences; Internal Medicine Sciences; Nuclear medicine; Klinik Tıp (MED); Klinik Tıp; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radiology, Nuclear Medicine and Imaging; Caudal regression syndrome; sacral agenesis; VACTERL association; Tc-99m DMSA renal scintigraphy; SPECT/CT; SCINTIGRAPHY; Sacral agenesis; Caudal regression syndrome; sacral agenesis; VACTERL association; Tc-99m DMSA renal scintigraphy; SPECT/CT; Kaudal regresyon sendromu; sakral agenezi; VACTERL asosiyasyonu; Tc-99m DMSA böbrek sintigrafisi; SPECT/BT